The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-89132003000300012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity and its influence on Copaifera langsdorffii Desf. (Caesalpiniaceae)

Abstract: Population dynamics and structure of young individuals of the tree Copaifera langsdorffii Desf. (Caesalpiniaceae) were studied in the gallery forest of the Panga Ecological Station, Uberlândia, MG, Brazil. Three distinct habitats were recognized in this forest, Dike, Middle and Edge zone. Four annual surveys of plant height, diameter at plant base and density were made between 1993 and 1996. The species showed an aggregated distribution in all three habitats. Population structure in all four surveys presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
3
2
10
Order By: Relevance
“…The shape of the diameter distribution of regeneration was not negative exponential (i.e., inverted J). Negative exponential diameter and height distributions for Copaifera regeneration were observed by Resende [12] and Rigamonti-Azevedo [46], unlike our results (Table 4). Resende et al [12] observed a change in distributional shape over a three year observation period, wherein the number of regenerating Copaifera in smaller diameter classes decreased, but increased in the largest diameter class.…”
Section: Effects Of Reduced-impact Logging On Diameter Distribution Ocontrasting
confidence: 99%
See 1 more Smart Citation
“…The shape of the diameter distribution of regeneration was not negative exponential (i.e., inverted J). Negative exponential diameter and height distributions for Copaifera regeneration were observed by Resende [12] and Rigamonti-Azevedo [46], unlike our results (Table 4). Resende et al [12] observed a change in distributional shape over a three year observation period, wherein the number of regenerating Copaifera in smaller diameter classes decreased, but increased in the largest diameter class.…”
Section: Effects Of Reduced-impact Logging On Diameter Distribution Ocontrasting
confidence: 99%
“…Negative exponential diameter and height distributions for Copaifera regeneration were observed by Resende [12] and Rigamonti-Azevedo [46], unlike our results (Table 4). Resende et al [12] observed a change in distributional shape over a three year observation period, wherein the number of regenerating Copaifera in smaller diameter classes decreased, but increased in the largest diameter class. However, we observed Copaifera regeneration presence in all diameter classes and an increasing number of recruits in the larger classes of managed stands, in contrast with unmanaged stands.…”
Section: Effects Of Reduced-impact Logging On Diameter Distribution Ocontrasting
confidence: 99%
“…Thus, propagules coming from other nonflooded communities can easily colonize swamp areas, especially those species with zoochorous dispersion [36]. A good example in the study area is Copaifera langsdorffii, more frequently found in nonflooded forests [21,37], but present in the seedling category. However, once plants start to grow and become sapling, the floristic composition changes remarkably in the studied swamp forest.…”
Section: Discussionmentioning
confidence: 99%
“…Finalizando, a estrutura espacial agregada dessas cinco populações corrobora com o padrão geral encontrado em outros estudos e revela-se dominante entre as espécies vegetais do Cerrado em diferentes escalas e fitofisionomias (Oliveira et al 1989, Meireles & Luiz 1995, Hay et al 2000, Resende et al 2003, Souza & Coimbra 2005, Costa 2006, LimaRibeiro 2007a, b, Lima-Ribeiro & Prado 2007. Além disso, o estudo evidencia influência do substrato no padrão de distribuição espacial dos indivíduos e sugere associação entre as espécies analisadas.…”
Section: Discussionunclassified
“…No Cerrado brasileiro, várias espécies vegetais tem mostrado um padrão de distribuição espacial agregado em diferentes escalas e localidades (Oliveira et al 1989, Meireles & Luiz 1995, Hay et al 2000, Resende et al 2003, Monteiro & Fisch 2005, Souza & Coimbra 2005, Lima-Ribeiro, 2007a, b, Lima-Ribeiro & Prado 2007. Este padrão de distribuição parece ser predominante entre as espécies arbóreo-arbustivas dos cerrados, indicando semelhanças entre os processos de estruturação e dinâmica populacional ocorrentes nas savanas em geral, onde a estrutura espacial dominante das espécies vegetais também é agregada, como descrito por San Jose et al (1991) para espécies arbóreas dos Llanos venezuelanos.…”
Section: Introductionunclassified